Rights of Nature and the Antarctic:philosophical considerations, possible modalities, and relations with the Antarctic Treaty System - Alvarez Ortega, Elena Laura; Makanse, Yousra; Bastmeijer, Kees (The Polar Journal, 2024)
This article identi!es and further discusses key themes and insights from The Polar Journal Special Issue on Rights of Nature and the Antarctic. First, philosophical considerations in relation to RoN are examined, with a speci!c focus on Antarctica’s intrinsic value and the question of whether RoN can be seen as an ecocentric or anthropocentric concept. Next, the possible modalities of an Antarctic RoN approach are examined, including questions on who should be rights holders and what rights are involved, distin- guishing between substantive and procedural rights. The analysis then turns to the question of how an Antarctic RoN approach would relate to the Antarctic Treaty System, with special attention to the draft Antarctica Declaration and the relationship between a RoN approach and the values and principles of the Antarctic Treaty and the Environmental Protocol. It is hoped that the discussions in this Special Issue will be a valuable addition to the ongoing debate regarding RoN worldwide and will contribute to the policy discus- sions on how to strengthen the protection of the Antarctic environment.